Health Behaviors of Cancer Survivors in Nationwide Cross-Sectional Survey in Korea: Higher Alcohol Drinking, Lower Smoking, and Physical Inactivity Pattern in Survivors with Higher Household Income - Park, Boyoung (Medicine (Baltimore), 2015)
This study investigated the prevalence of smoking, alcohol consumption, and physical activity in cancer survivors and examined the sociodemographic factors affecting these health-related behaviors. We used data from the 4th and 5th Korean National Health and Nutrition Examination Survey conducted between 2007 and 2012, which identified 1153 cancer cases and 36,451 people without a history of cancer ≥20 years of age. We used a structured questionnaire to obtain information concerning cancer diagnosis, health-related behaviors, and sociodemographic characteristics. The proportion of cancer survivors who were current drinkers, heavy drinkers, current smokers, or engaged in physical activity were 49.1, 9.0, 9.2, or 50.7%, respectively. Compared with people with no history of cancer, cancer survivors were less likely to be current drinkers (odds ratio [OR] = 0.45; 95% confidence interval [CI] 0.36–0.56), heavy drinkers (OR = 0.53; 95% CI 0.36–0.78), current smokers (OR = 0.37; 95% CI 0.24–0.55), or physically inactive (OR = 0.77; 95% CI 0.63–0.95). Cancer survivors with higher household incomes had higher odds of current drinking and heavy drinking (P trend = 0.039 and 0.033, respectively) and were less likely to be current smokers or physically inactive (P trend = 0.016 and 0.046, respectively). Age, sex, sites of cancer, and the time since diagnosis affected the health behaviors in cancer survivors. Furthermore, we confirmed that these unhealthy behaviors are interrelated. We found that household income had a bidirectional effect on health behaviors and confirmed an aggregation of unhealthy lifestyles. Identification of survivors vulnerable to unhealthy lifestyles, focusing on household income level would allow intervention programs to be more effective.